Relationship between serum total bilirubin and frailty in middle-aged and elderly individuals - Cunbao Ling; Cunbao Ling; Libing Tian; Chunyan Zhang; Chunyan Zhang; Yaping Tian (Frontiers in Medicine, 2025)
BackgroundIn recent years, the increasing number of elderly individuals has highlighted frailty as a significant public health issue. Although the potential health benefits of bilirubin in adults are recognized, studies on the link between bilirubin levels and frailty are sparse. This study explores the association between serum total bilirubin (STB) and frailty in individuals aged 45–85 who participated in the National Health and Nutrition Examination Survey (NHANES) from 2015 to 2020.Materials and methodsSTB levels were measured using the Jendrassik-Grof method. Frailty was evaluated using a frailty index that included 49 deficits across seven domains. Survey weighted logistic regression analyses and Restricted Cubic Spline (RCS) techniques were used to examine the relationship between STB and frailty. Subgroup analyses were performed to confirm the consistency of the observed association.ResultsThe study comprised a cohort of 8,603 individuals aged between 45 and 85 years, of whom 54.7% were female, and 3,037 were identified as frail. In models that were fully adjusted, each unit increase in STB was associated with a 5% reduction in the risk of frailty. Participants in the second and third tertiles of STB exhibited statistically significant lower odds of frailty compared to those in the lowest tertile, with odds ratios (ORs) of 0.75 and 0.59, respectively. RCS analysis revealed an L-shaped correlation between STB levels and frailty, exhibiting statistically significant non-linearity (P = 0.0075), with an inflection point at 17.1 μmol/L of STB (the upper limit of normal). Below this threshold, a negative correlation is evident, whereas a weak positive correlation is observed for values exceeding 17.1 μmol/L. Further subgroup analysis within the physiological range of bilirubin suggests that the negative association between STB and frailty is more pronounced in individuals younger than 60 years.ConclusionThis study reveals a negative relationship between STB levels and frailty among middle-aged and elderly individuals, suggesting that elevated bilirubin concentrations within the physiological range may reduce the risk of frailty.